An empirical examination of the mechanisms mediating between high performance work systems and the performance of Japanese organizations - TAKEUCHI, Riki (Institutional Knowledge at Singapore Management University, 2007)
The resource-based view of the firm and social exchange perspectives are invoked to hypothesize linkages among high-performance work systems, collective human capital, the degree of social exchange in an establishment, and establishment performance. The authors argue that high-performance work systems generate a high level of collective human capital and encourage a high degree of social exchange within an organization, and that these are positively related to the organization's overall performance. On the basis of a sample of Japanese establishments, the results provide support for the existence of these mediating mechanisms through which high-performance work systems affect overall establishment performance.